Cognitive functioning after pallidotomy for refractory Parkinson's disease - Perrine, K. (BMJ Group, 1998)
BACKGROUND—Earlier approaches to pallidotomy for refractory Parkinson's disease had significant complication rates. More recent approaches show fewer complications, but the effect of pallidotomy on cognition is unclear. The current study was conducted to examine the neuropsychological effects of unilateral pallidotomy. METHODS—Neuropsychological testing was performed on patients with medically refractory, predominantly unilateral Parkinson's disease at baseline and after unilateral ventral pallidotomy (n=28) or after an equivalent period without surgery in control patients (n=10). RESULTS—Pallidotomy patients showed no significant changes from baseline to retesting relative to the control group for any measure. Across all of the tests administered, only five of the surgery patients showed a significant decline, and of these five none declined on more than one test. Depression did not relate to preoperative or postoperative cognition. The pallidotomy group showed a significant improvement in motor functioning and activities of daily living whereas the control group did not. These measures were not associated with the neuropsychological test scores at baseline or retest. CONCLUSIONS—Stereotactic unilateral ventral pallidotomy does not seem to produce dramatic cognitive declines in most patients.